(untitled) (Revista Argentina de Musicología, 2001)
Since the end of the 1920’s and during the next decade, it is possible to recognize the impact of neoclassic and objectivist musical trends on the work or several Argentinean composers. This article analyzes the reception of the musical thought and the international repertoire of the lime, the productive ways in which they have been processed in the local works and their relationship with similar tendencies in other fields of the modernity in Buenos Aires. The text reflects on the meaning and scope of this kind of modernity in the context of the Argentinean music history and on the problems concerning its relationship with different historiographic and aesthetic paradigms.